Perilaku Ibu dalam Pemenuhan Kebutuhan Asah, Asih dan Asuh Anak dengan Leukemia - Praba Diyan Rachmawati; Reza Ranuh; Yuni Arief (Universitas Airlangga, 2016)
Introduction: Children with leukemia have a poor quality of live. A long term periode of care, treatment, side effect of treatment and the symptom of the leukemia disease will have an impact on leukemia children quality of life. Parents have an important role in meeting the basic needs of the child by stimulation, emotion and physical. With the fulfillment of the basic needs of children, the quality of life of children with leukemia will increase.Methods: Design used in this study was an observational analytic in Hematology room Dr. Soetomo Hospital. The population was mother of leukemia children Bona 1 hematology room in Dr Soetomo Hospital. Conducted on 17th April- 17th May 2014. Consecutive sampling was used in this study. Sample were 20 mother who met in inclusion criteria. Independent variables were mother’s characteristics, self efficacy source, family centre care, Parental Self efficacy and dependent variables were mother’s behaviour. Data was collected using quetionnaire and analyzed using PLS (Partial Least Square) Regression.Results: Result showed that sources of self-efficacy influence on self-efficacy, self efficacy and mother’s characteristics directly affects the mother’s behaviour. Family centered care can’t directly affect mother’s behaviour.Discussion: It can be concluded that mother’s behaviour model in stimulating, loving and physical caring children with leukemia can be formed from mother’s characteristics, self efficacy source and Parental self efficacy. Parental self efficacy can be increased especially by improving coping mechanisms and vicarious experience.